Boron isotopic signatures of melt inclusions from North Iceland reveal recycled material in the Icelandic mantle source. (1st February 2021) - Hartley, Margaret E.; de Hoog, Jan C.M.; Shorttle, Oliver
Highlights: A new estimate of the δ 11 B signature of ambient Reykjanes Ridge mantle: −6.1 ± 0.3‰. Icelandic mantle δ 11 B investigated using glassy melt inclusions. Mantle-derived δ 11 B only recorded in primitive (MgO > 8 wt.%) melt inclusions. Light δ 11 B (−10.6‰) in the Icelandic mantle derives from recycled subducted material. Light δ 11 B signature easily diluted by mixing with melts of depleted MORB mantle. Abstract: Trace element and volatile heterogeneity in the Earth's mantle is influenced by the recycling of oceanic lithosphere through subduction. Oceanic island basalts commonly have high concentrations of volatiles compared to mid-ocean ridge basalts, but the extent to which this enrichment is linked to recycled mantle domains remains unclear. Boron is an ideal tracer of recycled subducted material, since only a small percentage of a recycled component is required to modify the bulk δ 11 B of the source mantle. Boron isotopic compositions of primary melts thus have potential to trace the fate of recycled subducted material in the deep mantle, and to constrain the lengthscales of lithologic and compositional heterogeneities in diverse tectonic settings. We present new measurements of volatiles, light elements and boron isotopic ratios in basaltic glasses and melt inclusions that sample the mantle at two endmember spatial scales. Submarine glasses from the Reykjanes Ridge sample long-wavelength mantle heterogeneity on the broad scale of the Iceland plume. Crystal-hosted melt inclusions from the Askja and Bárðarbunga volcanic systems in North Iceland sample short-wavelength mantle heterogeneity close to the plume centre. The Reykjanes Ridge glasses record only very weak along-ridge enrichment in B content approaching Iceland, and there is no systematic variability in δ 11 B along the entire ridge segment. These observations constrain ambient Reykjanes Ridge mantle to have a δ 11 B of −6.1‰ (2SD = 1.5‰, 2SE = 0.3‰). The North Iceland melt inclusions have widely variable δ 11 B between −20.7 and +0.6‰. We screen melt inclusions against influence from crustal contamination, identifying high [B] and low δ 18 O as fingerprints of assimilation processes. Only the most primitive melt inclusions with MgO ⩾ 8 wt.% reliably record mantle-derived δ 11 B. In North Iceland, incompatible trace element (ITE)-depleted primitive melt inclusions from Holuhraun record a δ 11 B of −10.6‰, a signal that has also been seen in melt inclusions from southwest Iceland (Gurenko and Chaussidon, 1997). In contrast, primitive ITE-enriched melt inclusions from nearby Askja volcano record a δ 11 B of −5.7‰, overlapping with our new constraint on the δ 11 B of Reykjanes Ridge mantle. Coupled [B], δ 11 B and δ 18 O signatures of more evolved melt inclusions from North Iceland are consistent with primary melts assimilating <5–20% of hydrothermally altered basaltic hyaloclastite as they ascend through the upper crust. Our data reveal the presence of a depleted, low- δ 11 B and an enriched, higher- δ 11 B mantle component, both intrinsic to the Icelandic mantle source and distinct from Reykjanes Ridge mantle. Non-modal melting calculations suggest that the enriched and depleted mantle components both contain ∼0.085 μg/g B, slightly lower than the 0.10–0.11 μg/g calculated for Reykjanes Ridge mantle. These data are consistent with the Icelandic mantle containing B-depleted dehydrated recycled oceanic lithosphere, in keeping with the low B/Pr of Icelandic melt inclusions in comparison to Reykjanes Ridge glasses or MORB. Our new data provide strong support for the role of recycled subducted lithosphere in melt generation at ocean islands, and highlight the need for careful screening of melt inclusion compositions in order to study global volatile recycling in ocean island basalts.